Stage-based interventions for smoking cessation - Cahill, K; Lancaster, T; Green, N (JOHN WILEY and SONS LTD, 2010)
BackgroundThe transtheoretical model is the most widely known of several stage-based theories of behaviour. It proposes that smokers move through a discrete series of motivational stages before they quit successfully. These are precontemplation (no thoughts of quitting), contemplation (thinking about quitting), preparation (planning to quit in the next 30 days), action (quitting successfully for up to six months), and maintenance (no smoking for more than six months). According to this influential model, interventions which help people to stop smoking should be tailored to their stage of readiness to quit, and are designed to move them forward through subsequent stages to eventual success. People in the preparation and action stages of quitting would require different types of support from those in precontemplation or contemplation.ObjectivesOur primary objective was to test the effectiveness of stage-based interventions in helping smokers to quit.Search strategyWe searched the Cochrane Tobacco Addiction Group's specialised register for trials, using the terms ('stage* of change', 'transtheoretical model*', 'trans-theoretical model*, 'precaution adoption model*', 'health action model', 'processes of change questionnaire*', 'readiness to change', 'tailor*') and 'smoking' in the title or abstract, or as keywords. The latest search was in August 2010.Selection criteriaWe included randomized controlled trials, which compared stage-based interventions with non-stage-based controls, with 'usual care' or with assessment only. We excluded trials which did not report a minimum follow-up period of six months from start of treatment, and those which measured stage of change but did not modify their intervention in the light of it.Data collection and analysisWe extracted data in duplicate on the participants, the dose and duration of intervention, the outcome measures, the randomization procedure, concealment of allocation, and completeness of follow up.The main outcome was abstinence from smoking for at least six months. We used the most rigorous definition of abstinence, and preferred biochemically validated rates where reported. Where appropriate we performed meta-analysis to estimate a pooled risk ratio, using the Mantel-Haenszel fixed-effect model.Main resultsWe found 41 trials (>33,000 participants) which met our inclusion criteria. Four trials, which directly compared the same intervention in stage-based and standard versions, found no clear advantage for the staging component. Stage-based versus standard self-help materials (two trials) gave a relative risk (RR) of 0.93 (95% CI 0.62 to 1.39). Stage-based versus standard counselling (two trials) gave a relative risk of 1.00 (95% CI 0.82 to 1.22). Six trials of stage-based self-help systems versus any standard self-help support demonstrated a benefit for the staged groups, with an RR of 1.27 (95% CI 1.01 to 1.59). Twelve trials comparing stage-based self help with 'usual care' or assessment-only gave an RR of 1.32 (95% CI 1.17 to 1.48). Thirteen trials of stage-based individual counselling versus any control condition gave an RR of 1.24 (95% CI 1.08 to 1.42). These findings are consistent with the proven effectiveness of these interventions in their non-stage-based versions. The evidence was unclear for telephone counselling, interactive computer programmes or training of doctors or lay supporters. This uncertainty may be due in part to smaller numbers of trials.Authors' conclusionsBased on four trials using direct comparisons, stage-based self-help interventions (expert systems and/or tailored materials) and individual counselling were neither more nor less effective than their non-stage-based equivalents. Thirty-one trials of stage-based self help or counselling interventions versus any control condition demonstrated levels of effectiveness which were comparable with their non-stage-based counterparts. Providing these forms of practical support to those trying to quit appears to be more productive than not intervening. However, the additional value of adapting the intervention to the smoker's stage of change is uncertain. The evidence is not clear for other types of staged intervention, including telephone counselling, interactive computer programmes and training of physicians or lay supporters. The evidence does not support the restriction of quitting advice and encouragement only to those smokers perceived to be in the preparation and action stages.